2021
DOI: 10.1017/s1468109921000062
|View full text |Cite
|
Sign up to set email alerts
|

A different choice, a different outcome: budgetary effects of a conservative legislator in liberal local regions of South Korea

Abstract: In Korean society, regionalism has deep historical roots and has had a great influence on elections. A historic event occurred in 2014 when a conservative party candidate, Lee Jung-hyun, was elected as a member of the National Assembly in Suncheon-si, Jeollanam-do, where liberal parties have been in the midst of powerful political influence. This was possible because voters responded to the candidate's appeal to vote based on benefits to the local economy, that is, securing greater funding from the central gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 61 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Regions that have been historically isolated by geography and the use of dialects are more likely to present salient hometown preferences (Falck et al 2012; Michalopoulos 2012). These localities tend to have a strong culture and exhibit regional cleavages (Jung 2021; Hochul 2003). 14 I also excluded the samples from Busan when conducting the estimation.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Regions that have been historically isolated by geography and the use of dialects are more likely to present salient hometown preferences (Falck et al 2012; Michalopoulos 2012). These localities tend to have a strong culture and exhibit regional cleavages (Jung 2021; Hochul 2003). 14 I also excluded the samples from Busan when conducting the estimation.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Voters’ political preferences have converged with the regionally based party, with attachment to particular regional leaders. Such confrontations have further solidified through unequal resource allocation, such as government expenditure and elite recruitment (Ha and Lee, 2022; Hong and Park, 2016; Horiuchi and Lee, 2008; Jung, 2021; Kang, 2016; Kim, 2021). As party labels play a major role in garnering votes, and legislators are motivated to receive endorsement from their regionally dominant party and residents in the subsequent election, party–politician unity becomes stronger within the pork-centric regional party system (Shin and Lee, 2017).…”
Section: Theoretical Background and Application To Korean Contextmentioning
confidence: 99%
“…Under a long-standing authoritarian regime, political parties receive highly concentrated support from their home regions through bloc votes that have persisted over time (Kang and Jaung, 1999). For example, conservative party candidates for the National Assembly have only been elected three times in Jeolla Province since democratization in 1987 (Jung, 2021), and this trend continued into the 2022 presidential election. Such local partisan representation with regionalist partisan support has been further strengthened through unequal resource allocation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Government spending reflects policy priorities, and the mayor plays a critical role in budget allocation at the local level. As in many other countries (Levitt et al, 1997), local government leaders in South Korea have a great influence on budget formulation, and local public finance greatly affects the local economy and residents’ welfare (Jung, 2021; Kim et al, 2020). 2 Therefore, analyzing the amount and composition of government spending affected by female representation in leadership is crucial to understanding public policy direction and performance, and international organizations have suggested that the budget should reflect gender-sensitive features and their societal effects (Downes et al, 2017; Stotsky, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%